Healthy food access is more about affordability than proximity - Aurora Buffington; Millicent Braxton (Urban Food Systems Symposium, 2020)
Healthy food purchasing and consumption behaviors among low-income, low-access consumers are often attributed to the availability of healthy food retail outlets in their neighborhoods. However, studies suggest that the adage "if you build it, they will come" may not result in improved dietary intake and access because drivers of behavior are multi-faceted and not confined to the factor of proximity. With Extension professionals' guidance, a local food policy council subcommittee explored perceptions of food access among patrons of service providers located in low-income census tracts in Henderson, NV. The Council prepared a report based on their findings to help city planners assess residents' needs and desires living in and around identified food deserts as part of a REACH (Racial and Ethnic Approaches to Community Health) grant deliverable through a sponsorship with the local health department. Qualitative and quantitative data were obtained during three focus group sessions from 28 participants, which were mostly low-income, including two groups of seniors and one group of Hispanic mothers of young children. Participants filled out a 15-item pre-survey, and a 10-item open-ended discussion guide was used to facilitate the focus group discussions. The principal factor influencing food shopping was price/cost, quality, and location/convenience following correspondingly. Seventy-eight percent used neighborhood grocery stores as their primary place to get food; however, 75% stated they also used farmers markets, and 60% also used food pantries. Qualitative data showed that most participants had a good base of existing nutrition knowledge and desired what most consumers want: affordability, quality, selection, convenience, and safe, wholesome food. Themes emerging from the qualitative data analysis included health (current and future), planning, availability, influences on behavior, foods considered healthy or unhealthy, federal nutrition programs, and putting others' needs before their own. Preliminary findings show that these urban low-income, low-access consumers perceive their most significant barrier to obtaining healthy food is lack of money, not living in a food desert, or lack of nutrition knowledge. Ensuring residents in a food desert have employment opportunities created by adding a healthy food retail outlet in their neighborhood may be more meaningful than bringing in a business run by outsiders. City planners are challenged to explore ways to help low-income residents get a "leg-up" in their community through job creation and other forms of community development that create economic opportunity and increase access to good quality healthy food.
Keywords: qualitative; seniors; Hispanic; shopping; perception; neighborhood